Increasing Community Awareness About The Importance Of Stunting Education For Pkk Women In Lumut District, Lumut District, Central Tapanuli District - Hasian Rambe; Luthfi Ilham Martua Lumban Tobing; Rahmiatul Zuhro; Zuhrina Harahap (Edumaspul: Jurnal Pendidikan, 2023)
Lumut Village is a village located in Lumut District, Central Tapanuli Regency, North Sumatra. The majority of the people's livelihoods in Lumut Village are farmers. The area of ​​this moss village is one of the areas with a high prevalence in Central Tapanuli District. With this problem in mind, this journal aims to develop people's thinking by educating or providing information through the UIN SU 156 community service group to the community, especially mothers in the Lumut sub-district about how to prevent stunting, with the hope that the prevalence the rate of stunting in the Lumut District area will decrease. which is used in the context of providing education to mothers is by conducting socialization, the socialization material is provided by the KKN 156 UIN-SU group and assisted by stunting management in the Lumut Village area.